The relationship between conference presentations and in-hospital mortality in patients admitted with acute myocardial infarction: A retrospective analysis using a Japanese administrative database. - Daisuke Takada; Yuki Kataoka; Tetsuji Morishita; Noriko Sasaki; Susumu Kunisawa; Yuichi Imanaka (PLoS ONE)
Background Clinicians' research activities reportedly improve their healthcare performance. Presenting research at conferences may be related to improved patient care outcomes; however, few studies have investigated this relationship. Thus, we examined the association between presenting at conferences and the mortality of patients hospitalized for acute myocardial infarction. Methods We analyzed an administrative database of acute care hospitals in Japan. The study compared patients admitted to hospitals in which physicians made at least one conference presentation during the patient's admission year (Presentation Group) with those admitted to hospitals with no conference presentations (Control group). We performed multivariable logistic regression analyses to estimate the risk of all-cause in-hospital mortality. Five models were fitted: a Crude model, unadjusted; Model 1, adjusted for personal factors, including sex, age, Killip classification, and so on; Model 2, adjusted for Model 1 plus hospital factors; Model 3 was a multilevel analysis clustered by hospital codes and adjusted for the same variables as Model 1; Model 4 was adjusted for Model 1 plus evidence-based practices through causal mediation analysis. Results After excluding 3,544 patients with missing Killip classification or ambulance use, data for 56,923 patients in 384 acute care hospitals were analyzed. Drug prescription in accordance with the evidence was significantly greater in the Presentation group than in the Control group. Moreover, conference presentation was significantly associated with lower in-hospital mortality in all models (Odds ratios (OR) = 0.68, 95% Confidence intervals (CIs): 0.65 to 0.72 in the Crude model; OR = 0.73, 95% CIs: 0.68 to 0.79 in Model 1; OR = 0.76, 95% CIs: 0.70 to 0.82 in Model 2; OR = 0.84, 95% CIs: 0.76 to 0.92 in Model 3; OR = 1.00, 95% CIs: 0.92 to 1.09 in Model 4). Conclusion The promotion of scholarly activities such as conference presentations might improve patient outcomes through increased evidence-based practice.